1985
DOI: 10.1038/clpt.1985.131
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and dynamics of disopyramide and its dealkylated metabolite in healthy subjects

Abstract: The kinetics and dynamics of total and free (unbound) disopyramide (D) after dosing with D, 1.5 and 2 mg/kg iv, were compared with those of the dealkylated metabolite (MND) after dosing with MND, 0.5 and 1.5 mg/kg iv, in six healthy subjects. Dynamic parameters included ECG with measurement of the QT interval corrected for heart rate (QTc), systolic time intervals, vitamin C-stimulated saliva secretion, pupil size, and maximum accommodation capacity. Mean values of total clearance, apparent volume of distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…Available data from humans support these findings. For example, it has been shown that better linear relationships exist between free disopyramide concentrations (than total drug) and measured pharmacological response, including change in QT c (Chiang et al 1985;Thibonnier et al 1984) and negative inotropic effect (Chiang et al 1985;Holt et al 1983b;Lima et al 1981;Pollick et al 1982). Thus, when monitoring disopyramide plasma concentration, it appears that it may be more relevant to monitor free rather than total concentration.…”
Section: Disopyramidementioning
confidence: 92%
See 2 more Smart Citations
“…Available data from humans support these findings. For example, it has been shown that better linear relationships exist between free disopyramide concentrations (than total drug) and measured pharmacological response, including change in QT c (Chiang et al 1985;Thibonnier et al 1984) and negative inotropic effect (Chiang et al 1985;Holt et al 1983b;Lima et al 1981;Pollick et al 1982). Thus, when monitoring disopyramide plasma concentration, it appears that it may be more relevant to monitor free rather than total concentration.…”
Section: Disopyramidementioning
confidence: 92%
“…It has the interesting property of concentration-dependent binding at therapeutic plasma concentrations (Hinderling & Garrett 1976). The disopyramide free fraction has been reported to vary from 0.10 to 0.40 over a given dosage interval in an individual (Bredesen et al 1982;Bredesen & Kierulf 1984;Chiang et al 1985). Thus, the clearance of total disopyramide exhibits apparent dose-dependent behaviour (Hinderling & Garrett 1976), while clearance of unbound disopyramide is a nearly linear function of dose (Lima et al 1981;Meffin et al 1979).…”
Section: Disopyramidementioning
confidence: 93%
See 1 more Smart Citation
“…It is excreted in the urine mostly unchanged, but 20-50% is metabolized. Considering the pharmacological activity of the metabolite, as observed in experimental models and noninvasively in humans [3][4][5], it could be assumed to contribute significantly to the effects during maintenance t r e a tment with disopyramide in individual patients. The steadystate ratio of the metabolite to the p a r e n t drug ranged between 0.06 and 4.0 in the plasma of 70 patients and was ->1.0 in more than 25% of patients [2].…”
mentioning
confidence: 99%
“…The major metabolite is des-isopropyldisopyramide, usually called mono-N-dealkylated disopyramide [1]. However, neither the class 1 electrophysiologic effects of the metabolite nor its anticholinergic actions, claimed to be 3-24 times more pronounced than those of the parent drug [3,4], have been appropriately assessed by invasive electrophysiologic methods in human beings. Considering the pharmacological activity of the metabolite, as observed in experimental models and noninvasively in humans [3][4][5], it could be assumed to contribute significantly to the effects during maintenance t r e a tment with disopyramide in individual patients.…”
mentioning
confidence: 99%